2022
DOI: 10.1007/s00330-021-08465-w
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to differentiate small round cell malignant tumors and non-small round cell malignant tumors of the nasal and paranasal sinuses using apparent diffusion coefficient values

Abstract: Objective We used radiomics feature–based machine learning classifiers of apparent diffusion coefficient (ADC) maps to differentiate small round cell malignant tumors (SRCMTs) and non-SRCMTs of the nasal and paranasal sinuses. Materials A total of 267 features were extracted from each region of interest (ROI). Datasets were randomized into two sets, a training set (∼70%) and a test set (∼30%). We performed dimensional reductions using the Pearson correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Recent studies have demonstrated that segmentation repeatability is essential in terms of feature stability, for it is heavily influenced by different MRI protocols and machines [ 21 , 33 , 34 , 35 , 36 ]. In this paper, we downloaded the segmented data outlined on the TCIA website by using automatic image segmentation and manual supervision, and we performed the experiment using the FAE software, which is a publicly available tool for radiomics models and is applied to many fields [ 37 , 38 , 39 , 40 , 41 ]. Thus, all the experiment results are robust and replicable.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that segmentation repeatability is essential in terms of feature stability, for it is heavily influenced by different MRI protocols and machines [ 21 , 33 , 34 , 35 , 36 ]. In this paper, we downloaded the segmented data outlined on the TCIA website by using automatic image segmentation and manual supervision, and we performed the experiment using the FAE software, which is a publicly available tool for radiomics models and is applied to many fields [ 37 , 38 , 39 , 40 , 41 ]. Thus, all the experiment results are robust and replicable.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have combined AI with CT 20,21,35,44,46,47,53,56,69,80 . Other studies have combined AI with MRI, 33,39,40,45 whole‐slide imaging (WSI), 14,15,51 endoscopic images, 82,90 or positron emission tomography (PET)‐CT 34 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies used AI to differentiate anterior ethmoidal artery location, 20 identify middle turbinate pneumatization (concha bullosa), 21 and recognize and calculate the volume of the inferior turbinate and maxillary sinus. 53 Most studies have combined AI with CT. 20,21,35,44,46,47,53,56,69,80 Other studies have combined AI with MRI, 33,39,40,45 whole-slide imaging (WSI), 14,15,51 endoscopic images, 82,90 or positron emission tomography (PET)-CT. 34 Some studies directly compared AI with specialist physicians and showed equivalence or superiority of AI over specialist physicians 14,69,80,90 ; it was found that AI required much less time to diagnose. 14 Some studies have combined 2 or more algorithms to solve this problem.…”
Section: Application Of Ai In Rhinologymentioning
confidence: 99%
“…Radiomics performs high-throughput mining and quantification of medical images, extracts, and analyses of almost infinite advanced quantitative features by identifying tumor heterogeneity and microenvironment, thus contributing to the detection, diagnosis, and assessment of cancer 17,18 . The applications of radiomics for the head and neck have demonstrated promising results in the differential diagnosis of malignant tumors 19–23 . To the best of our knowledge, no studies yet use the approach of radiomics to identify these 2 types of sinonasal NHLs.…”
mentioning
confidence: 99%
“…17,18 The applications of radiomics for the head and neck have demonstrated promising results in the differential diagnosis of malignant tumors. [19][20][21][22][23] To the best of our knowledge, no studies yet use the approach of radiomics to identify these 2 types of sinonasal NHLs.…”
mentioning
confidence: 99%